Thermoelectric properties of a magnetic semiconductor CuFeS2. (December 2017) - Takaki, Hirokazu; Kobayashi, Kazuaki; Shimono, Masato; Kobayashi, Nobuhiko; Hirose, Kenji; Tsujii, Naohito; Mori, Takao
Abstract: We present theoretical calculations of the thermoelectric properties of a magnetic semi-conductor CuFeS2 . The electrical contributions, namely the Seebeck coefficients, electrical conductances, and electronic thermal conductances, are investigated using first-principles calculation techniques based on density functional theory and the nonequilibrium Green's function formalism. The lattice thermal transport properties are analyzed using the nonequilbirium molecular dynamics simulation method. Using a combination of the calculated electronic contributions and the lattice thermal contribution, the thermoelectric figures of merit are calculated and analyzed in doped configurations for the theoretical prediction of the highest thermoelectic energy conversion efficiency. It is shown that dilute doping enhances the figure of merit by 2.5 times compared to 3% doping which was previously experimentally obtained to give the best thermoelectric performance among samples studied. Graphical abstract: Highlights: Thermoelectric properties of magnetic semiconductor CuFeS2 are analyzed by theory. Enhancement of figure of merit ZT by carrier doping is theoretically demonstrated. Dilute doping enhances ZT by 2.5 times than the best experimental result.